Physiological Responses and Dynamic Hyperinflation Induced by Unsupported Arm Activities Involved in Multiple-Task Activities of Daily Living Test in Patients With COPD. Issue 6 (November 2018) - Gulart, Aline Almeida; Munari, Anelise Bauer; dos Santos, Karoliny; Tressoldi, Caroline; Karloh, Manuela; Mayer, Anamaria Fleig
Abstract : Purpose: This study aimed to analyze the isolated role of unsupported arm activities and the physiological responses and dynamic hyperinflation (DH) induced by activities of daily living in patients with chronic obstructive pulmonary disease. Physiological responses and DH were compared using the Glittre activities of daily living test (TGlittre) and a modified protocol that emphasized unsupported arm activities and excluded squats and bending down to move objects on shelves (TGlittre-M). Data were also compared from the isolated shelf tasks of TGlittre (TSHELF ) and TGlittre-M (TSHELF-M ). Methods: This cross-sectional study included 30 patients with chronic obstructive pulmonary disease who performed the TGlittre, TGlittre-M, TSHELF and TSHELF-M . The physiological responses were evaluated during the 4 protocols and inspiratory capacity was measured before and immediately after the tests for evaluation of DH. Results: Patients had higher oxygen uptake, ventilatory demand, dyspnea, and DH in the TGlittre than in the TGlittre-M (mean differences: 123 ± 119 mL/min; 0.11 ± 0.10, 1 [−1 to 3], and − 0.14 ± 0.22, respectively; P < .05 for all). Oxygen uptake, ventilatory demand, and dyspnea were also higher in the TSHELF than in the TSHELF-M (mean differences: 408 ± 185 mL/min; 0.26 ± 0.17; 1 [−1 to 3], respectively; P < .05 for all). However, DH was similar for both tasks ( P > .05). Conclusions: In patients with chronic obstructive pulmonary disease, the physiological demands during unsupported arm activities were lower than during the task performed with squatting and bending down; however, the magnitude of DH did not differ between them. These results suggest that the isolated arm activities contribute less to the TGlittre's physiological requirement than the lower-limb and trunk activities. Abstract : This study analyzed the isolated role of unsupported arm activities in the physiological responses and dynamic hyperinflation induced by the Glittre activities of daily living test (TGlittre) in patients with chronic obstructive pulmonary disease. It seems that isolated arm activities contribute less to the physiological requirements of TGlittre than the leg and trunk activities.